A Potential Role of Cytomegalovirus Reactivation in the Severity of COVID-19 in the Elderly - Tehrani, Shabnam; Keyvanfar, Amirreza (Novelty in Biomedicine, 2022)
In late 2019, severe acute respiratory syndrome- coronavirus-2 (SARS-CoV-2) was reported in Wuhan, China. This virus spread quickly worldwide, with millions of victims until now. The clinical manifestations of the novel coronavirus disease (COVID-19) are a broad spectrum, from asymptomatic and mild cases with a flu-like syndrome to severe cases requiring intensive care1. The severity of diseases and risk of mortality is higher in the elderly, which most authorities attribute to underlying conditions, including diabetes, hypertension, cardiovascular diseases, and respiratory diseases. However, some neglected factors, such as cytomegalovirus (CMV) reactivation, can affect patient outcomes2.